Ad Astra – telomeres in space!. (4th March 2022) - Bailey, Susan M.; Luxton, Jared J.; McKenna, Miles J.; Taylor, Lynn E.; George, Kerry A.; Jhavar, Sameer G.; Swanson, Gregory P.
Abstract: Purpose: My journey to the stars began as I – along with the whole world – stood still and watched Neil Armstrong take those first small steps on the Moon. Fast forward 50 years and NASA astronauts Scott Kelly and Christina Koch each spend nearly a year in space aboard the International Space Station (ISS), a remarkable multinational collaborative project and floating U.S. National Laboratory that has supported continuous human presence in low Earth orbit for the past 20 years. Marking a new era of human space exploration, the first commercial rocket, SpaceX Falcon 9, recently launched NASA astronauts Doug Hurley and Bob Behnken in the Crew Dragon spacecraft Endeavor to the ISS and returned safely to Earth. NASA and its commercial partners are rapidly advancing innovative space technologies, and with the recently announced Artemis team of astronauts, plans to send the first woman and next man back to the moon and establish sustainable exploration by the end of the decade. Humankind will then be poised to take the next giant leap – pioneering human exploration of Mars. Conclusions: Historically, fewer than 600 individuals have participated in spaceflight, the vast majority of whom have been middle aged males (35-55 years) on short duration missions (less than 20 days). Thus, as the number and diversity of space travelers increase, a better understanding of how long-duration spaceflight affects human health is essential to maintaining individual astronaut performance during, and improving disease and aging trajectories following, future exploration missions. Here, I review findings from our NASA Twins Study and Telomeres investigations, highlighting potential mechanistic roles of chronic space radiation exposure in changes in telomere length and persistent DNA damage responses associated with long-duration spaceflight. Importantly, similar trends were observed in prostate cancer patients undergoing intensity-modulated radiation therapy (IMRT), additional support specifically for the role of radiation exposure. Individual differences in response were also observed in both cohorts, underscoring the importance of developing personalized approaches for evaluating human health effects and long-term outcomes associated with radiation exposures, whether on Earth or living in the extreme environment of space.